Relationships between Kováts Retention Indices and Molecular Descriptors of 1-(2-Hydroxy)-3-Arylpropane-1,3-Diones - Gustavo P. Romanelli; Jorge L. Jios; Juan C. Autino; Lázaro F.R. Cafferata; Eduardo A. Castro (The Scientific World Journal)
Experimental and theoretical results for retention index of a set of 20 beta-diketones are given. The quantitative structure-chromatographic retention relationships (QSRR) theory is employed and six molecular descriptors are chosen to compute the fitting polynomials. Multiple regression analysis yields satisfactory results when one resorts to several variables equations, instead of computing just one-variable formulae. Average absolute deviations from experimental results are rather low, which seems to point out the suitability of the present approach.